Konflik sosial dan lingkungan di sektor energi terbarukan: Tinjauan pada skala global - Hannysyah Roesdi; Rahmawati Lestari; Ratna Amini (Institute for Advanced Science Social, and Sustainable Future, 2024)
The increasing social and environmental issues and the depletion of natural resources have led many countries to shift from using non-renewable energy sources (fossil fuels) to renewable energy sources (solar energy, geothermal, etc.). This energy transition is aimed at sustainable practices. However, the process poses new social, economic, and environmental challenges that policymakers must address effectively. Economic support from the government is a key factor in the success of implementing this transition. Nevertheless, it is undeniable that the shift to renewable energy has generated social conflicts among stakeholders, such as debates over the construction of power plants that are perceived to have limited benefits for the communities around the plant area. The need for renewable energy arises as a solution to the insufficient electricity supply in developing countries, especially in rural areas. Various stakeholders offer solutions to overcome social challenges in the community during this transition. The objective of this literature review is to identify and analyze social and environmental issues arising from the transition from non-renewable to renewable energy sources. The results obtained will be presented descriptively, supplemented with matrices or tables. The articles used in this study draw examples from the implementation of renewable energy transitions in various countries such as Taiwan, Canada, Brazil, Poland, South Korea, Indonesia, and others. The challenges faced by each country in implementing renewable energy transitions exhibit similarities, and the solutions used to mitigate these challenges also share commonalities.